Multiomics, pharmacogenomic, and structural characterization of NCCRP1 as a candidate therapeutic target in ovarian cancer - Dahlak Daniel Solomon; Yung-Kuo Lee; Sachin Kumar; Kai-Fu Chang; Chung-Hsien Lin; Ching-Chung Ko; Ngoc Uyen Nhi Nguyen; Do Thi Minh Xuan; Neethu Palekkode; Chih-Yang Wang; Hui-Ru Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Phylogeny and taxonomic revisions of Piper (Piperaceae) in Taiwan - Po-Hao Chen; Chia-Hao Chang; Kuan-Ning Kung; Hung‑Chih Lin; An-Ching Chung; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Research, 2026)
Taiwan, located at the northernmost extent of Huxley’s Line, marks the furthest point along this biogeographic boundary where exchanges of flora and fauna occur. The genus Piper , a globally distributed and taxonomically complex group of both economic and evolutionary importance, has a convoluted taxonomic history in this transitional zone that requires comprehensive study. Here, we integrate morphological, molecular, and distributional data to revise the taxonomy of Taiwanese Piper , resolve their evolutionary relationships, and infer their biogeographic history. Our revision recognizes 11 species in Taiwan, including seven native taxa, of which three are endemic. The present analysis establishes the first comprehensive phylogenetic framework for Taiwanese Piper and reveals that native species arose from lineages on both sides of Wallace’s Line. Collectively, these findings provide the first evidence of bidirectional expansion within a genus in Taiwan and position Piper as an exemplary system for examining phylogeographic dynamics in transitional biogeographic zones.

Circular economy and financial risk in cement manufacturing: A path toward SDG 7 - Xuelian Li; Yujie Cai; Ching-Hui Chang; Jyh-Horng Lin (Journal of Environmental Management, 2026)

Coupling fine-scale molecular approaches with hydrodynamic modeling to inform conservation management of the endangered and endemic fiddler crab Xeruca formosensis - Kun-Ching Hung; Hui-Chen Lin (Journal of Environmental Management, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Middle Eocene arc magmatism from Armenia with new insights into tectonic evolution of the Arabia-Eurasia collision zone - Yu-Chin Lin; Kwan-Nang Pang; Ghazar Galoyan; Rafael Melkonyan; Hao-Yang Lee; Ching-Hua Lo; Jin-Hui Yang; Sun-Lin Chung (Lithos, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

Formononetin protects against oxaliplatin-induced peripheral neurotoxicity via Nrf2/HO-1 antioxidant pathway without impairing anticancer efficacy - Yang-Chen Chang; Wan-Hsuan Lin; Horng-Huey Ko; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Yih-Fung Chen (NeuroToxicology, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Entropy-stabilized multi-element 2D TMDs: Tunable electronics and enhanced thermal stability - Ching-Wei Chin; Chong-Chi Chi; Kai-Yuan Hsiao; Yi-Hsin Fang; Dun-Jie Jhan; Chun-Hui Lin; Ming-Pei Lu; Ming-Yen Lu (Chemical Engineering Journal, 2025)

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Segmentation of the Manila subduction zone and slab tearing beneath the Philippine mobile belt - Shu-Kun Hsu; Wen-Nan Wu; Lien-Kai Lin; Shiou-Ya Wang; Yi-Ching Yeh; Leo T. Armada; Carla B. Dimalanta; Kuan-Ting Chen; Yun-Jie Tsai; Ching-Hui Tsai (Journal of Asian Earth Sciences, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Rapid evaluation of apigenin bioavailability and hypouricemic bioactivity by targeted metabolomics study in enterohepatic microenvironment mimetic cell culture model - Su-Jung Hsu; Hui-Chen Chung; Chia-Hsuan Chang; Yi-Chi Liao; Ta-Wei Liu; Shu-Mei Lin; Ching-Kuo Lee (Food Research International, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

Validation of Automated Standardization Performance for ECDaim Software Developed Using a Taiwan-Specific Database - Yu-Ching Ni; Hui-Chieh Yang; Ing-Tsung Hsiao; Fan-Pin Tseng; Chia-Yu Lin; Wen-Bin Lin; Zong-Jhe Lyu (Journal of Medical and Biological Engineering, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Energy transition: Cap-and-trade and carbon capture and storage for achieving net-zero emissions with sustainable insurance - Shi Chen; Yuqi Li; Jyh-Horng Lin; Ching-Hui Chang (Journal of Environmental Management, 2024)

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Material flow analysis of commercial fishing gears in Taiwan - Ching-Tuan Su; Falk Schneider; Paritosh C. Deshpande; Hui-Ya Xiao; Tien-An Su; Ning Yen; Hsin-Tien Lin (Marine Pollution Bulletin, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

An efficient cellular image-based platform for high-content screening of neuroprotective agents against chemotherapy-induced neuropathy - Yang-Chen Chang; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Chien-Chih Chiu; Yih-Fung Chen (NeuroToxicology, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Seasonal Distributions of Methane in a Populous Urban Coastal Sea Area - Hsiao-Chun Tseng; Chia-Chia Lin; Hui-Juan Pan; Yokie Tai Yuh Han; Gwo-Ching Gong (Frontiers in Marine Science, 2022)
Methane (CH 4 ) is an important greenhouse gas, and its concentrations in aquatic areas are heavily influenced by anthropogenic activities, especially human-induced eutrophication, polluted river discharge and wastewater treatment plant (WWTP) effluents. Although coastal areas and estuaries contribute large amounts of global oceanic CH 4 emissions, the relative contributions of different sources have not been well determined. The Tamsui River located in northern Taiwan is an urban river flowing through populated cities and thus likely carries large amounts of contaminants, such as nutrients and organic matter to the estuary. In this study, we characterized the spatial distribution and seasonal variations in CH 4 in the Tamsui River estuary adjacent marine areas. The sea-to-air CH 4 fluxes were also estimated to quantify the strength of the study area as an atmospheric CH 4 source. Our results showed that CH 4 concentrations in coastal sea areas were influenced by WWTP effluents, sediment and freshwater inputs. Thus, river discharge and nutrient levels as well as strong vertical mixing and disturbances might increase CH 4 concentrations and emissions. The seasonal surface CH 4 concentrations and sea-to-air CH 4 fluxes were 13.7 ± 18.7 nM and 41.7 ± 68.0 μmol m -2 d -1 in autumn; 29.3 ± 19.8 nM and 61.3 ± 44.6 μmol m -2 d -1 in spring; 21.8 ± 13.9 nM and 37.0 ± 26.2 μmol m -2 d -1 in summer; and 27.0 ± 21.4 nM and 85.9 ± 75.4 μmol m -2 d -1 in winter.

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

Twist1 Plays an Anti-apoptotic Role in Mutant Huntingtin Expression Striatal Progenitor Cells - Wei-Ping Jen; Hui-Mei Chen; Yow-Sien Lin; Yijuang Chern; Yi-Ching Lee (Molecular Neurobiology, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Progressive multifocal leukoencephalopathy in a renal transplant patient - Tsu-Chen Lin; Mei-Yi Wu; Hui-Tzung Luh; Shiou-Fu Lin; Chien-Min Lin; Ying-Chi Tseng; Yung-Ching Liu; Mai-Szu Wu (Journal of NeuroVirology, 2019)

Genetic Deletion of Soluble Epoxide Hydroxylase Causes Anxiety-Like Behaviors in Mice - Hsueh-Te Lee; Kuan-I Lee; Hui-Ching Lin; Tzong-Shyuan Lee (Molecular Neurobiology, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Soluble Epoxide Hydrolase Inhibition Attenuates MPTP-Induced Neurotoxicity in the Nigrostriatal Dopaminergic System: Involvement of α-Synuclein Aggregation and ER Stress - Hui-Ju Huang; Yi-Ting Wang; Hui-Ching Lin; Yi-Hsuan Lee; Anya Maan-Yuh Lin (Molecular Neurobiology, 2018)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Loss of Transient Receptor Potential Ankyrin 1 Channel Deregulates Emotion, Learning and Memory, Cognition, and Social Behavior in Mice - Kuan-I Lee; Hui-Ching Lin; Hsueh-Te Lee; Feng-Chuan Tsai; Tzong-Shyuan Lee (Molecular Neurobiology, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

The relationship between plasma and urinary 8-hydroxy-2-deoxyguanosine biomarkers measured by liquid chromatography tandem mass spectrometry - Chung-Ching Wang; Wei-Liang Chen; Chien-Ming Lin; Ching-Huang Lai; Ching-Hui Loh; Hong-I Chen; Saou-Hsing Liou (Environmental Science and Pollution Research, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Combined effect of rice genotypes and soil characteristics on iron plaque formation related to Pb uptake by rice in paddy soils - Fang-Lin Li; Ching-Ming Yang; Chien-Hui Syu; Dar-Yuan Lee; Ben-Jei Tsuang; Kai-Wei Juang (Journal of Soils and Sediments, 2016)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

BK Induces cPLA2 Expression via an Autocrine Loop Involving COX-2-Derived PGE2 in Rat Brain Astrocytes - Chih-Chung Lin; Hsi-Lung Hsieh; Shiau-Wen Liu; Hui-Ching Tseng; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Identification and characterization of a novel chloroplast/mitochondria co-localized glutathione reductase 3 involved in salt stress response in rice - Tsung-Meng Wu; Wan-Rong Lin; Yun-Ting Kao; Yi-Ting Hsu; Ching-Hui Yeh; Chwan-Yang Hong; Ching Huei Kao (Plant Molecular Biology, 2013)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Coexisting mutations/polymorphisms of the long QT syndrome genes in patients with repaired Tetralogy of Fallot are associated with the risks of life-threatening events - Shuenn-Nan Chiu; Mei-Hwan Wu; Ming-Jai Su; Jou-Kou Wang; Ming-Tai Lin; Chien-Chih Chang; Hui-Wen Hsu; Ching-Tsuen Shen; Olivier Thériault; Mohamed Chahine (Human Genetics, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Trace metal cycling in the surface water of the South China Sea: Vertical fluxes, composition, and sources - Tung-Yuan Ho; Wen-Chen Chou; Ching-Ling Wei; Fei-Jan Lin; George T. F. Wong; Hui-Ling Line (Limnology and Oceanography, 2010)
We deployed floating traps in the surface waters of the South China Sea on four occasions at depths of 30 m, 100 m, and 160 m from 2006 to 2007 to quantify vertical metal fluxes in the surface water and examine trace metal composition in the sinking particles to investigate their sources. The elements determined include 13 trace metals and 8 major elements. The fluxes for most of the bioactive elements at 30 m varied markedly during different seasons and strongly co‐varied with organic matter production, but the fluxes at 160 m were low and consistent under different seasons, showing that most of the elements were internally recycled in the surface water during productive seasons. Most of the bioactive trace metals in sinking particles were correlated with biogenic P, and their P‐normalized quotas were also strongly associated with lithogenic Al. The ratios of metals to Al and P for most of the bioactive trace metals were significantly higher than the ratios in lithogenic particles and than intracellular quotas in plankton, respectively, indicating that the trace metals in the sinking particles were abiogenic, nonlithogenic, and adsorbed on biogenic particles. The comparable fluxes between aeolian deposition and the sinking particles in the mixed layer demonstrate that the highly enriched trace metals in the sinking particles were attributed to input from anthropogenic aerosols. The coupling and transport of anthropogenic trace metals with biogenic particles in oceanic surface waters may be an important mechanism for trace metal cycling in global oceans.

Erratum to: Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Lin; Shuan-Yow Li (Human Genetics, 2010)

Increasing trend of the incidence of esophageal squamous cell carcinoma, but not adenocarcinoma, in Taiwan - Ching-Liang Lu; Hui-Chu Lang; Jiing-Chyuan Luo; Chun-Chu Liu; Han-Chieh Lin; Full-Young Chang; Shou-Dong Lee (Cancer Causes & Control, 2010)

A Reproductive Toxicology Study of Phenanthrene in Medaka (Oryzias latipes) - Ching-Yi Horng; Hui-Chen Lin; Wenjau Lee (Archives of Environmental Contamination and Toxicology, 2010)

Naringenin-Loaded Nanoparticles Improve the Physicochemical Properties and the Hepatoprotective Effects of Naringenin in Orally-Administered Rats with CCl4-Induced Acute Liver Failure - Feng-Lin Yen; Tzu-Hui Wu; Liang-Tzung Lin; Thau-Ming Cham; Chun-Ching Lin (Pharmaceutical Research, 2009)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Genetic analysis of an attenuated Papaya ringspot virus strain applied for cross-protection - Chu-Hui Chiang; Chun-Yee Lee; Ching-Hsien Wang; Fuh-Jyh Jan; Shih-Shun Lin; Tsung-Chi Chen; Joseph A. J. Raja; Shyi-Dong Yeh (European Journal of Plant Pathology, 2007)

Characterization of the genomic structures and selective expression profiles of nine class I small heat shock protein genes clustered on two chromosomes in rice (Oryza sativa L.) - Jiahn-Chou Guan; Tsung-Luo Jinn; Ching-Hui Yeh; Shi-Pin Feng; Yih-Ming Chen; Chu-Yung Lin (Plant Molecular Biology, 2004)

A Method for Locating Influential Pollution Sources and Estimating Their Contributions - Ching-Ho Lin; Yee-Lin Wu; Ken-Hui Chang; Chin-Hsing Lai (Environmental Modeling & Assessment, 2004)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Wogonin and fisetin induction of apoptosis through activation of caspase 3 cascade and alternative expression of p21 protein in hepatocellular carcinoma cells SK-HEP-1 - Yen-Chou Chen; Shing-Chuan Shen; Woan-Rouh Lee; Hui-Yi Lin; Ching-Huai Ko; Chun-Ming Shih; Ling-Ling Yang (Archives of Toxicology, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)